2021
DOI: 10.1111/1471-0307.12833
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecularly imprinted solid‐phase extraction coupled with liquid chromatography method for detection of penicillin G in pasteurised milk samples

Abstract: In the present study, a polymeric powder, synthesised using methacrylic acid as the functional monomer and ethylene glycol dimethacrylate as the cross-linker, was used as a highly selective sorbent in a molecularly imprinted solid-phase extraction cartridge to extract penicillin G from milk samples. Detection was performed using high performance liquid chromatography. The proposed method was used to determine penicillin G in the milk matrix in the range of 3-1000 ng/mL (limit of detection 2 ng/mL) with relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The applications of MISPE and MIP sensors for the analytical determination of antibiotic residues are comprehensively reviewed according to the different kinds of SAs, QNs, BALs, MALs, TCs, AGs and others. Some typical examples of MISPE in antibiotic analysis are listed in Table 1 [10,11,23,40,42,45,49,51,56,59,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95], and MIP-based electrochemical sensors and optical sensors for antibiotic analysis are shown in Table 2 [68][69][70]72,[96][97][98][99][100][101][102][103][104][105][106][107] and Table 3 [74,76,…”
Section: Applications Of Mips For Antibiotic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The applications of MISPE and MIP sensors for the analytical determination of antibiotic residues are comprehensively reviewed according to the different kinds of SAs, QNs, BALs, MALs, TCs, AGs and others. Some typical examples of MISPE in antibiotic analysis are listed in Table 1 [10,11,23,40,42,45,49,51,56,59,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95], and MIP-based electrochemical sensors and optical sensors for antibiotic analysis are shown in Table 2 [68][69][70]72,[96][97][98][99][100][101][102][103][104][105][106][107] and Table 3 [74,76,…”
Section: Applications Of Mips For Antibiotic Analysismentioning
confidence: 99%
“…Pourtaghi et al [80] prepared MIPs using penicillin G (PEN-G) as a template, MAA as a functional monomer and EGDMA as a cross-linker, as an adsorbent for SPE, combined with HPLC-UV, to detect PEN-G in milk samples. The results showed that the LOD was 2 ng/mL and the relative recoveries were 81-90%.…”
Section: Balsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first antibiotic to be utilized in veterinary medication was penicillin G, which was at first made accessible in 1947 (Samad, 2022). Misuse of this antibiotics may led to the resistance and residues in dairy products (Pourtaghi et al, 2022). Poor quality milk containing the ABs poses threat to the one health and public health.…”
Section: Introductionmentioning
confidence: 99%